A SACRIFICE BEYOND BORDERS: HONORING THE INDONESIAN DOCTOR KILLED WHILE SERVING IN PALESTINE - Asti Dwiyanti; Fikal Adriansyah Hadamu, Adhani Swastika Utami, Flaviana Kidi Sili Lamatokan, Valerisandi Paundanan (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This article examines the tragic case of an Indonesian doctor who was killed while providing humanitarian medical services in Palestine, shedding light on the dangers faced by healthcare professionals in conflict zones. The study explores the broader context of humanitarian crises, the role of medical workers, and the risks they encounter in environments where international humanitarian law is frequently violated. By utilizing a literature review methodology, the article synthesizes existing research on the protection of healthcare workers, the impact of conflict on medical infrastructures, and Indonesia’s humanitarian diplomacy. The findings highlight the essential contributions of medical professionals in war-torn regions and the urgent need for stronger international protections. The article also underscores the challenges of delivering aid in conflict zones, especially Palestine, where political and security factors impede effective humanitarian interventions. In addition, it calls for a renewed global commitment to safeguarding medical personnel, enhancing legal enforcement, and ensuring the safety of healthcare workers operating in high-risk areas. Ultimately, the article honors the memory of the Indonesian doctor and advocates for a more robust international framework to protect those who risk their lives to save others